Impatience is a Virtue: Revisiting Disorder in High-Performance Log Analytics - Chandramouli, Badrish; Goldstein, Jonathan; Li, Yinan (34th IEEE International Conference on Data Engineering (ICDE 2018), Paris, France, 2018)
There is a growing interest in processing real-time queries over out-of-order streams in this big data era. This paper presents a comprehensive solution to meet this requirement. Our solution is based on Impatience sort, an online sorting technique that is based on an old technique called Patience sort. Impatience sort is tailored for incrementally sorting streaming datasets that present themselves as almost sorted, usually due to network delays and machine failures. With several optimizations, our solution can adapt to both input streams and query logic. Further, we develop a new Impatience framework that leverages Impatience sort to reduce the latency and memory usage of query execution, and supports a range of user latency requirements, without compromising on query completeness and throughput, while leveraging existing efficient in-order streaming engines and operators. We evaluate our proposed solution in Trill, a high-performance streaming engine, and demonstrate that our techniques significantly improve sorting performance and reduce memory usage – in some cases, by over an order of magnitude.